Co-exposure with CeO2NPs results in an antagonistic effect on the cytotoxicity and genotoxicity of TiO2NP on A549 cells - Rosário, Fernanda (2022)
Objective: Assess the CYTOTOXIC and GENOTOXIC POTENTIAL resulting from titanium dioxide nanoparticles (TiO2NP) and cerium oxide nanoparticles (CeO2NP) co-exposure in human lung epithelial cell line A549.